Antifilarial and antibiotic activities of Methanolic extracts of Melaleuca cajuputi flowers - Al-Abd, N.M.; Zurainee, M.N.; Mansor, M.; Hasan, M.S.; Kassim, M. (Korean Society of Parasitology, 2016)
We evaluated the activity of methanolic extracts of Melaleuca cajuputi flowers against the filarial worm Brugia pahangi and its bacterial endosymbiont Wolbachia. Anti-Wolbachia activity was measured in worms and in Aedes albopictus Aa23 cells by PCR, electron microscopy, and other biological assays. In particular, microfilarial release, worm motility, and viability were determined. M. cajuputi flower extracts were found to significantly reduce Wolbachia endosymbionts in Aa23 cells, Wolbachia surface protein, and microfilarial release, as well as the viability and motility of adult worms. Anti-Wolbachia activity was further confirmed by observation of degraded and phagocytized Wolbachia in worms treated with the flower extracts. The data provided in vitro and in vivo evidence that M. cajuputi flower extracts inhibit Wolbachia, an activity that may be exploited as an alternative strategy to treat human lymphatic filariasis.